Conserving wildlife : international education and communication approaches (Dehradun, 2003)
This volume explores fifteen exemplary education and communication programs that have contributed to the conservation of wildlife and natural resources around the world, presenting the perspectives necessary to confront the unubated extinction of animal and plant species and increasing human pressure on tropical and temperate forests, wetlands, and marine environments. The contributors include documented examples of conservation education programs, with sections on planning, implementing, and assessing each program..
Keywords: Wildlife cnservation